Top-quark pair production cross sections and calibration of the top-quark Monte-Carlo mass : measurements performed with the CMS detector using LHC run I Proton-Proton collision data /: measurements performed with the CMS detector using LHC run I Proton-Proton collision data. (2016) - Kieseler, Jan
No abstract available